Methylglyoxal induces p53 activation and inhibits mTORC1 in human umbilical vein endothelial cells - Zhang, Xinmiao; Rodriguez-Niño, Angelica; Pastene, Diego O.; Pallavi, Prama; van den Born, Jacob; Bakker, Stephan J. L.; Krämer, Bernhard; Yard, Benito A. (Scientific reports, 2021)
Methylglyoxal (MGO), a precursor of advanced glycation end products (AGEs), is regarded as a pivotal mediator of vascular damage in patients with diabetes. We have previously reported that MGO induces transcriptional changes compatible with p53 activation in cultured human endothelial cells. To further substantiate this finding and to explore the underlying mechanisms and possible consequences of p53 activation, we aimed (1) to provide direct evidence for p53 activation in MGO-treated human umbilical vein endothelial cells (HUVECs), (2) to assess putative mechanisms by which this occurs, (3) to analyze down-stream effects on mTOR and autophagy pathways, and (4) to assess the potential benefit of carnosine herein. Exposure of HUVECs to 800 µM of MGO for 5 h induced p53 phosphorylation. This was paralleled by an increase in TUNEL and γ-H2AX positive cells, indicative for DNA damage. Compatible with p53 activation, MGO treatment resulted in cell cycle arrest, inhibition of mTORC1 and induction of autophagy. Carnosine co-treatment did not counteract MGO-driven effects. In conclusion, our results demonstrate that MGO elicits DNA damage and p53 activation in HUVECs, resulting in modulation of downstream pathways, e.g. mTORC1.
Gesehen am 03.08.2021